The A.C. electrical response from the grain and grain boundary components of a Li0.25Ni0.2Zn0.3Fe2.25O4 ferrite - Ahmad Nazlim Yusoff ,; Mustaffa Hj. Abdullah, (Universiti Kebangsaan Malaysia, 1997)
The a.c. electrical response of a polycrystalline Li0.25Ni0.2Zn0.3Fe2.25O4 ferrite is studied by means of impedance spectroscopy. The impedance measurement was performed at different input voltage amplitudes in ten decades of frequency (1 mHz - 10 MHz). Two overlapping semicircles with negative capacitance phenomenon below 1 Hz are observed at all amplitudes. The two semicircles are mainly attributed to the grain and grain boundary processes at high and low frequencies respectively. The grain boundary impedance shows a non-linear dependence on the input voltage, where the corresponding impedance semicircle is smaller for larger amplitude. However, a linear response is observed for the grain component. The dependence of the a.c. electrical properties of the grain and grain boundary components on the amplitude of the input voltage is discussed.